Dermatomyositis: A case report - Meenakshi Kalyan; Shubhangi A Kanitkar; Anu N Gaikwad; Harsh Kumar (Wolters Kluwer Medknow Publications, 2016)
Dermatomyositis is an idiopathic inflammatory myopathy involving proximal muscle weakness and non-suppurative skeletal muscle inflammation. Classification of dermatomyositis for a definitive diagnosis requires characteristic rash and other criteria, such as proximal muscle weakness and muscle enzyme level elevation. Muscle biopsy is central in establishing the diagnosis. In this article, we report a case of dermatomyositis without coexisting cancer, which is rare.